2020
DOI: 10.1007/s12678-020-00600-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Tailor-Made Hydrocarbons from Organic Solvent Free Aqueous Fatty Acid Mixtures in a Micro Flow Reactor

Abstract: The process described in the current paper is an alternative route that allows running the Kolbe electrolysis under economically attractive conditions and thus bringing it closer to an industrial application through novel process conditions, novel reactor technology, and the utilization of low-cost excess renewable electricity. The process allows the conversion of fatty acids into hydrocarbons in aqueous electrolytes without applying organic solvents. Important process parameters such as electrode material cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Hence, at very high current densities, higher flow rates should be applied, increasing the mass transfer and improving the removal of gas bubbles to maintain high Kolbe selectivity. In addition, it was also shown that high hydroxide ion concentrations (high pH value) do not necessarily implicate in the formation of non‐Kolbe products like alcohols (aldehydes) or esters, which has been also shown in one of our previous works [22] and had been studied in detail by Harnisch et al [18] . Despite the discussed results, we could reach a very high selectivity for Kolbe products (>91 %) in the investigated current density range, and the detected differences where only small.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Hence, at very high current densities, higher flow rates should be applied, increasing the mass transfer and improving the removal of gas bubbles to maintain high Kolbe selectivity. In addition, it was also shown that high hydroxide ion concentrations (high pH value) do not necessarily implicate in the formation of non‐Kolbe products like alcohols (aldehydes) or esters, which has been also shown in one of our previous works [22] and had been studied in detail by Harnisch et al [18] . Despite the discussed results, we could reach a very high selectivity for Kolbe products (>91 %) in the investigated current density range, and the detected differences where only small.…”
Section: Resultssupporting
confidence: 74%
“…In addition, phase separation allows a direct recycling of the aqueous phase in a continuous operation where reactant is constantly added. [ 20 , 21 , 22 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G. Yuan et al 14 demonstrated that the selective production of hydrocarbons with different chain lengths could be achieved by designing 3D nanoscale Pt anodes with preferred orientations, for the biomass-derived n -octatonic acids in aqueous media via Kolbe electrolysis. Depending on the fatty acid mixtures (C 5 –C 9 ) chosen, A. Ziogas et al 15 obtained the tailor-made products of hydrocarbons through Kolbe electrolysis in aqueous electrolytes without organic solvents by using the microstructured reactors. Recently, D. Klüh et al 16 proposed the basic engineering design on a continuously working process for three different feedstocks (acetic acid, valeric acid and lauric acid), and it was confirmed that the long-chain fatty acids are favorable as feedstock, concerning the best carbon yield and lowest product-specific charge.…”
Section: Introductionmentioning
confidence: 99%
“…These olefins include important monomers like propylene [12,13] or ethyl acrylate [3], whereas oxygenated products show promising applications in fuel design [4] or fine chemical industry [6]. While the general reaction con-ditions of (Non-)Kolbe electrolysis were thoroughly studied [7,8], current research focuses on the substrate scope [14,15], economical and ecologically improved anodes [3,16], and sophisticated reaction engineering like in situ product separation [3,9,10] or continuous processes [10,17,18]. The Non-Kolbe electrolysis of monomethyl succinic acid enables a sustainable pathway to methyl acrylate, which is used in textile industry.…”
Section: Introductionmentioning
confidence: 99%